The effectiveness of E-Payment transactions using encrypted QR code - Nur ‘Athirah Nazarudin; Nur ‘Atiqah Radzuan; Nur Adibah Mansor; Nur Afiqahizzati Poh Lee (2022)
E-payment can be defined as the other way to paying goods or services. People are no need to go out to get it instead they can order and get it through online. It is very easy to use where the user just needs electronic devices such as computers, smartphones or tablets to make any online transactions. Along with the advancement of technology, e-payment has also undergone technological changes where it has changed from the use of credit or debit cards and bank transfers to the use of QR codes to conduct transactions. QR codes are believed to have many special features that can improve the way e-payments operate. The objective and primarily aim of this research are to study the effect of access information, convenient and security to the effectiveness of QR code in e-payment. This current study adopted quantitative methodology and collect data from 269 respondents from Year 3 students under Faculty of Entrepreneurship and Business in University Malaysia Kelantan.